2018
DOI: 10.18699/vj18.31-o
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a strategy for tumor-initiating stem cell eradication in primary human glioblastoma cultures as a model

Abstract: Primary cultures of human glioblastoma were obtained from the surgical material of patients K. (female, 61 years, Ds: relapse of glioblastoma) and Zh. (female, 60 years, Ds: relapse of glioblastoma). The effectiveness of a new therapeutic approach aimed at destroying the cancer cell community was evaluated on the primary cell lines of human glioblastoma culture by employing a new strategy of tumor-initiating stem cell synchronization and a domestic strategy of their eradication "3+1". The key elements of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The peak number of DSBs was observed 18 h after exposure to MMC ( P < 0.001) ( Figure 1E ). This pattern differed from that obtained for the primary cell culture 33 ; thus, an independent therapeutic scheme for treating U87 cells based on the new data regarding the repair of MMC-induced ICLs has been developed ( Figure 1F ).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The peak number of DSBs was observed 18 h after exposure to MMC ( P < 0.001) ( Figure 1E ). This pattern differed from that obtained for the primary cell culture 33 ; thus, an independent therapeutic scheme for treating U87 cells based on the new data regarding the repair of MMC-induced ICLs has been developed ( Figure 1F ).…”
Section: Resultsmentioning
confidence: 71%
“…The first three exposures result in the large-scale caspase-activated DNase-dependent apoptosis of committed and partially stem-like tumor cells, as we have demonstrated in Krebs-2 and some other experimental tumors. The fourth terminal exposure is supposed to completely eliminate the remaining tumor cells, including the TAMRA+ CSCs, observed in the Krebs-2 model 28 , 31 , 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, addition of the DNAmix leads to a massive lysis of committed cancer cells. This technology has been successfully tested on several experimental mouse and human cancers and in 3 pilot clinical cases (6,8,(76)(77)(78)(79).…”
Section: Cmld Cp-based Chemotherapymentioning
confidence: 99%
“…It has been incontrovertibly shown that systemic anticancer immunity is boosted by such therapy ( 6 , 8 , 77 ). Nonetheless, Karanahan technology is largely based on the eradication of TISCs and induction of massive apoptosis of committed cancer cells, rather than on anticancer immunity.…”
Section: Dnamix and Cp Treatments Are Core Elements Of The Karanahan Technology And Cmld Cp-based Chemotherapymentioning
confidence: 99%